Distribuição de renda de agricultores da Zona da Mata, Minas Gerais — 1977/84 - Moreira Leite, Carlos Antônio; Mukole, Kongolo; Batista de Oliveira, Evonir; de Lima, João Eustáquio (Revista Ceres, 2025)
This paper addresses income distribution issues and policy options of the Integrated Rural Development Program of the Zona da Mata, MG, PRODEMATA, to eliminate poverty and income inequality among the farmers assisted by this program.